2003
DOI: 10.1093/emboj/cdg047
|View full text |Cite
|
Sign up to set email alerts
|

Molecular evidence for a positive role of Spt4 in transcription elongation

Abstract: We have previously shown that yeast mutants of the THO complex have a defect in gene expression, observed as an impairment of lacZ transcription. Here we analyze the ability of mutants of different transcription elongation factors to transcribe lacZ. We found that spt4Delta, like THO mutants, impaired transcription of lacZ and of long and GC-rich DNA sequences fused to the GAL1 promoter. Using a newly developed in vitro transcription elongation assay, we show that Spt4 is required in elongation. There is a fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
97
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(105 citation statements)
references
References 56 publications
(92 reference statements)
8
97
0
Order By: Relevance
“…Spt4͞5 has been shown to act both positively and negatively on elongation by Pol II (8,9,11,13). The results of our ChIP analysis formally suggest that the processivity of Pol I is decreased Ϸ2-fold by the spt4⌬ mutation (Fig.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Spt4͞5 has been shown to act both positively and negatively on elongation by Pol II (8,9,11,13). The results of our ChIP analysis formally suggest that the processivity of Pol I is decreased Ϸ2-fold by the spt4⌬ mutation (Fig.…”
Section: Discussionsupporting
confidence: 69%
“…However, Spt4p and Spt5p also form a separate complex, devoid of Spt6p, that associates with Pol II physically and genetically, and this interaction is important for transcription elongation (8). More recent work has shown that deletion of the nonessential gene SPT4 results in reduced efficiency of Pol II elongation through GC-rich DNA sequences (9) and a general decrease in Pol II processivity (10). Taken together, all of these data clearly support a role for Spt4͞5 in transcription elongation by Pol II in yeast.…”
mentioning
confidence: 99%
“…Cells carrying mutations in SPT4 and SPT5 genes display phenotypes associated with defects in transcription elongation (39), and the gene products are thought to be involved directly in transcription elongation (30,32). However, the suppression of Rad26-independent TCR by Spt4-Spt5 does not seem to be achieved simply by stimulating transcription.…”
Section: Discussionmentioning
confidence: 99%
“…Immunoprecipitation studies showed that Spt4 and Spt5 form a complex, which physically interacts with Pol II (30). Yeast cells lacking Spt4 show reduced efficiency of Pol II elongation through GC-rich DNA sequences and a general decrease in Pol II processivity (31,32). These proteins are conserved eukaryotic transcription-elongation factors and are generally required for normal development and viral gene expression in multicellular eukaryotes (33).…”
mentioning
confidence: 99%
“…By contrast, Spt4 is a small polypeptide (100-120 amino acids) and is nonessential for cell growth in budding yeast (Malone et al 1993). Yeast spt4D cells display pleiotropic phenotypes that are probably linked to defects in transcription elongation and RNA processing (Rondó n et al 2003;Lindstrom et al 2003;Mason and Struhl 2005;Qui et al 2006;Schneider et al 2006). Many genetic interactions with spt4D have been observed in budding yeast (Saccharomyces Genome Database, www.yeastgenome.org).…”
Section: Introductionmentioning
confidence: 99%